Deterministic and Stochastic Analysis of a Ratio-Dependent Predator-Prey System with Delay - Maiti, A.; Jana, M. M. M.; Samanta, G. P. P. (Nonlinear Analysis: Modelling and Control, 2007)
Recently ratio-dependent predator-prey models have become the focus of considerable attention in theoretical ecology in their own right. In this paper, we have studied the deterministic and stochastic dynamical aspects of stability of a MichaelisMenten type ratio-dependent predator-prey system that includes discrete time-delay. Computer simulations are carried out to explain the analytical findings in deterministic environment. The biological implications of our analytical and numerical findings are discussed critically.
Keywords: predator-prey model; ratio-dependence; time-delay; stability; bifurcation; white noise